Downregulated Expression of CLEC9A as Novel Biomarkers for Lung Adenocarcinoma - Miao, Fang; Lou, Zhiguo; Ji, Shuhua; Wang, Dan; Sun, Yaolan; Liu, Huan; Yang, Chenggang (Frontiers in Oncology, 2021)
Purpose: Abnormal CLEC9A expression is concerned with carcinogenesis. However, the role of CLEC9A in lung adenocarcinoma (LUAD) remains unknown. This study aims to reveal the role of CLEC9A in LUAD based on bioinformatics and cellular functional experiments. Patients and methods: Data available from the Cancer Genome Atlas (TCGA) were employed to study CLEC9A expression and mutations in LUAD. Expression and alterations of CLEC9A was analyzed using UALCAN and cBioPortal, respectively. Protein protein interaction (PPI) network was built using GeneMANIA analysis. The similar genes of CLEC9A was obtained using GEPIA analysis, while Co-expression genes correlated with CLEC9A was identified using LinkedOmics analysis. We adopted A549 and BEAS-2B cells to CLEC9A transfection. MTT assay was used to detect the effect of CLEC9A on cell viability. Results: CLEC9A is down-regulated and the CLEC9A gene often altered in LUAD. The similar genes of CLEC9A were linked to functional networks involving positive regulation of interleukin-12 production, plasma membrane and CD40 receptor binding, primary immunodeficiency, intestinal immune network for IgA production and cell adhesion molecules pathways. Cell cycle, apoptosis, EMT and RAS/MAPK were significantly enriched pathways in positive and negative correlations genes with CLEC9A. After transfection, CLEC9A was remarkably increased in A549 and BEAS-2B cells. CLEC9A overexpression remarkably inhibited growth rate of A549 cells, while CLEC9A overexpression had no significant effect on the growth rate of BEAS-2B cells. Conclusion: CLEC9A overexpression inhibits cell proliferation in LUAD, suggesting that CLEC9A may be considered as a novel biomarkers for LUAD.